Awareness on Teratogenic Effects of Isotretinoin and Compliance with Precautionary Measures among Women of Childbearing Age in Makkah Province, Saudi Arabia - Rawan Al-Mekhlafi; Rawabi E. Attiyah; Yara R. Haddad; Louai A. Salah (Obstetrics and Gynecology International)
Acne vulgaris ranks among the most common dermatologic conditions encountered during adolescence up to adulthood. For moderate to severe cases of acne, isotretinoin is indicated as it is considered the most efficacious medication against acne. However, isotretinoin use is known to have its side effects and most importantly is the drug’s teratogenic potential. As a response, programs such as the Retinoid Pregnancy Prevention Program (PPP), System to Manage Accutane-Related Teratogenicity (SMART), and iPLEDGE were put into action as attempts to promote awareness on isotretinoin’s teratogenicity and reduce the incidence of exposed pregnancies. Such programs are lacking in Saudi Arabia. This study aimed, therefore, to evaluate the awareness of women of childbearing age in Makkah Province, Saudi Arabia, with regards to the side effects of the medication, specifically its teratogenicity. This study also intended to assess the compliance of both doctors and patients with the recommendations and precautions associated with isotretinoin. A cross-sectional study was conducted on 766 women participants using a previously validated questionnaire. Results showed that majority of the respondents (91%) are generally aware of the side effects of isotretinoin use, particularly its teratogenicity. However, lapses have been identified with regards to the compliance of both the treating physician and the patient. Three-fourths of sexually active women did not use any form of contraception while being on isotretinoin treatment. Two-thirds of the study participants responded that they were not issued approval forms indicating their understanding of the side effects of isotretinoin and the importance of compliance to the treating physician’s instructions; 11.5% claimed that their doctors did not perform any blood tests; and 67.7% claimed that no pregnancy test was performed at any time during the treatment. These findings strongly suggest a need for improvement when it comes to compliance of both doctors and patients. It is recommended that doctor-patient communication be more comprehensive and more efforts should be made to follow international guidelines in that regard.